Education for Sustainability: A 5E Lesson on the Water Cycle Introduces Elementary Preservice Teachers to Think about Their Impacts on Earth’s Fresh Water Supply - Trendell Nation, Molly; Davis, Jeni (Innovations in Science Teacher Education, 2016)
The following lesson demonstrates the use of a 5E learning cycle to teach elementary preservice teachers (PSTs) the basic principles of the water cycle and scientific modeling. An Education for Sustainability (EfS) approach was utilized to further engage students in thinking about human impact and the implications we have on this natural process. Through this classroom activity, PSTs were able to explore Earth’s water system and the consequential social effects on water availability, cleanliness, and sustainability worldwide.